Materials for EFL: Using Ads in English Classes - Helda Alicia Hidalgo Dávila; Magda L. Caicedo Vela (Asociación Colombiana de Profesores de Ingles, 2016)
Materials definitely play an important role in the process of teaching/learning a foreign language. The term itself refers to anything which is used by teachers and students to facilitate the learning of a language.